Impact of institutional diversity on unions and NGO's efforts to represent and articulate farm workers' grievances: case study of the 2012 Western Cape farm workers strike and protest action - Zvoutete, Jackie Tatenda (Department of Sociology, 2014)
Following a disconcerting pattern in South Africa's recent labour history, a violent strike and protests gripped the De Doorns area in the Hex Valley River Valley of Western Cape Province in the late months of 2012 and early 2013. Literature on collective action and mobilisation shows that many of these incidents are triggered by occasions where there is a clash or disagreement of interests between groups. The existence of groups with diverging interests creates the basis of conflict;; this dichotomy is the initial form of diversity. Through debunking and qualitatively analysing the role and responsibilities of the worker representative groups during the strikes, the study reveals that there is a weak representation structure which is worsened due to the diverse interests of the institutions. This ultimately negatively affects the process of attaining a practical solution for the farm workers' issues. The paper explores the layered disparities of the workers within the farms, showing that a group's view is an aggregation of individuals' different opinions and experiences;; this is important to acknowledge in the study of conflict. This dissertation is a presentation of the need for an adoption and inclusion of institutional diversity in the study of labour conflict in South Africa. Racial lines prominently draw diversity within a South African setting but this study proposes that diversity in other forms is crucial in understanding these protest situations and in seeking solutions. The paper makes this suggestion through an observation of the 2012 Western Cape Farm Worker Strike and protest action, by questioning how worker representative groups handled the responsibility of representing and articulating farm worker problems. Although each party may believe they are doing what is best for the farm workers plight, they each have different operational values and they strongly embody their own interests. This varied mix of agenda's and modes of operation leads to a lack of constructive dialogue. This break in effectual communication plays a role in weakening the representational abilities of the unions and organisations and consequently abates the possibilities of attaining the practicable resolutions which are best for the group that the parties claim to represent;; the farm workers. The paper identifies this as a problem and subsequently suggests an immediate evaluation of communication methods from all these parties in order to improve negotiations in the future. This thesis not designed as a solution but functions as a presentation or a sketch of the complex milieu that surround strikes and protest action in order to encourage new ways of thinking about farm disputes and ways to resolve them.